(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
TransInformação Vol. 25, n. 2 (2013) Link de acesso ao número http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/issue/view/278